Exploring The Experiences Of Caregivers And Formal Foster Parents Caring For Orphans And Vulnerable Children In The Akuapim South District - Allou, A.N. (University Of Ghana, 2021)
Globally, caring for orphans and vulnerable children (OVC) is one of the vital elements of social work practice. However, the experiences of caregivers and formal foster parents of OVC is almost a missing component in the child welfare system and research in Ghana. This study sought to: (a) find out the motivations of caregivers and formal foster parents, (b) identify the challenges faced by caregivers and formal foster parents, (c) explore the coping strategies employed by caregivers and formal foster parents and (d) ascertain the support systems available to caregivers and formal foster parents in the Akuapim South District. Adopting a qualitative research design, purposive sampling was used to recruit 26 participants for the study. The sample consisted of 16 caregivers from two residential homes, six formal foster parents and four social welfare officials from the Akuapim South’s Department of Social Welfare. In-depth interviews were utilised to gather data for the study. Using a thematic approach in analysing the data, the findings from this study showed that participants were motivated to care for as a result of religious beliefs and a sense of fulfilling social responsibilities. Both caregivers and formal foster parents indicated that managing behavioural problems of OVC was a greater challenge to them of which they resorted to punishing and dialoguing with the children. The study revealed that formal foster parents received more support from family and friends which motivates their future decision to continue caring for OVC. However, due to high organisational workload and work-family challenges, caregivers feel demotivated to continue caring for OVC. This study therefore recommends that the Ministry of Gender, Children and Social Protection and social workers to provide support services and training to effectively ensure the proper wellbeing of caregivers and formal foster parents.
MPhil. Social Work
Keywords: Akuapim South District; Caregivers; Formal Foster Parents; Orphans; Vulnerable Children